3 views (last 30 days)
Alex on 4 Apr 2012
Hey all,
I've been debugging this code for a while now, but I can't for the life of my find out what's wrong with this. Whenever I run into a MuPAD error, Mybest solution is usually to come here, so I'm here again? Can someone look through this code and help me out a bit? More eyes are always better, and I'd love to learn more about fixing MuPAD errors. Here's the code:
assert (mod(size(data, 1), 1) == 0, ...
'Input data must have an integer multiple of 1 rows');
assert (size(data, 2) == 8, ...
'Input data must have exactly eight columns.');
syms d1;
nsys = size(data, 1);
for k = 1 : nsys,
F = solve_d_two_layers_eq(data((k-1) + (1:1), 1:end));
d(k, :) = solve(F);
end
dd = double(d);
fid=fopen('d_values.csv','w');
fprintf(fid,'%+5.5f, %+5.5fi\n',[real(dd(:)), imag(dd(:))].');
fclose(fid);
And the function file:
function F = solve_d_two_layers_eq(p)
assert (ndims(p) ==2, ...
'System parameters ''p'' must be 2D matrix.');
assert (all(size(p) ==[1,8]), ...
'System parameters must be 1-by-8 matrix.');
syms d1
n0 = 1;
y = p(:,1);
R = p(:,2);
n1 = p(:,3);
k1 = p(:,4);
n2 = p(:,5);
k2 = p(:,6);
n3 = p(:,7);
k3 = p(:,8);
d2 = 300;
g1 = (n0.^2 - n1.^2 - k1.^2)./((n1 + n2).^2 + k1.^2);
g2 = (n1.^2 - n2.^2 + k1.^2 - k2.^2)./((n1 + n2).^2 + (k1 + k2).^2);
h1 = (2.*n0.*k1)./((n0 + n1).^2 + k1.^2);
h2 = (2.*(n1.*k2 - n2.*k1))./((n1 + n2).^2 + (k1 + k2).^2);
a1 = (2.*pi().*k1.*d1)./y;
b1 = (2.*pi().*n1.*d1)./y;
p2 = (exp(a1)).*cos(b1);
q2 = (exp(a1)).*sin(b1);
t2 = (exp(-1.*a1)).*(g2.*(cos(b1)) + h2.*(sin(b1)));
u2 = (exp(-1.*a1)).*(h2.*(cos(b1)) - g2.*(sin(b1)));
p12 = p2 + g1.*t2 - h1.*u2;
q12 = q2 + h1.*t2 + g1.*u2;
t12 = t2 + g1.*p2 - h1.*q2;
u12 = u2 + h1.*p2 + g1.*q2;
g3 = (n2.^2 - n3.^2 + k2.^2 - k3.^2)./((n2 + n3).^2 + (k2 + k3).^2);
h3 = (2.*(n2.*k3 - n3.*k2))./((n2 + n3).^2 + (k2 + k3).^2);
a2 = (2.*pi().*k2.*d2)./y;
b2 = (2.*pi().*n2.*d2)./y;
p3 = (exp(a2)).*(cos(b2));
q3 = (exp(a2)).*(sin(b2));
t3 = (exp(-1.*a2)).*(g3.*(cos(b2)) + h3.*(sin(b2)));
u3 = (exp(-1.*a2)).*(h3.*(cos(b2)) - g3.*(sin(b2)));
r2 = (exp(a1)).*(g2.*(cos(b1)) - h2.*(sin(b1)));
s2 = (exp(a1)).*(h2.*(cos(b1)) + g2.*(sin(b1)));
v2 = (exp(-1.*a1)).*(cos(b1));
w2 = (-1.*(exp(-1.*a1))).*(sin(b1));
r12 = r2 + g1.*v2 - h1.*w2;
s12 = s2 + h1.*v2 + g1.*w2;
v12 = v2 + g1.*r2 - h1.*s2;
w12 = w2 + h1.*r2 + g1.*s2;
p13 = p12.*p3 - q12.*q3 + r12.*t3 - s12.*u3;
q13 = q12.*p3 + p12.*q3 + s12.*t3 + r12.*u3;
t13 = t12.*p3 - u12.*q3 + v12.*t3 - w12.*u3;
u13 = u12.*p3 + t12.*q3 + w12.*t3 + v12.*u3;
F = (t13.^2 + u13.^2)./(p13.^2 + q13.^2) - R;
Alexander on 5 Apr 2012
What error message do you get?